If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 14)(2x + -7) = 0 Reorder the terms: (14 + x)(2x + -7) = 0 Reorder the terms: (14 + x)(-7 + 2x) = 0 Multiply (14 + x) * (-7 + 2x) (14(-7 + 2x) + x(-7 + 2x)) = 0 ((-7 * 14 + 2x * 14) + x(-7 + 2x)) = 0 ((-98 + 28x) + x(-7 + 2x)) = 0 (-98 + 28x + (-7 * x + 2x * x)) = 0 (-98 + 28x + (-7x + 2x2)) = 0 Combine like terms: 28x + -7x = 21x (-98 + 21x + 2x2) = 0 Solving -98 + 21x + 2x2 = 0 Solving for variable 'x'. Factor a trinomial. (-14 + -1x)(7 + -2x) = 0Subproblem 1
Set the factor '(-14 + -1x)' equal to zero and attempt to solve: Simplifying -14 + -1x = 0 Solving -14 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -1x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -1x = 0 + 14 -1x = 0 + 14 Combine like terms: 0 + 14 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14Subproblem 2
Set the factor '(7 + -2x)' equal to zero and attempt to solve: Simplifying 7 + -2x = 0 Solving 7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 0 + -7 -2x = 0 + -7 Combine like terms: 0 + -7 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5Solution
x = {-14, 3.5}
| -5g=-10-3g | | x^2-2x=16 | | 5x+9=2x+48 | | 12=3(y-6)+3y | | -5q=-3q+10 | | 52x^2+13=0 | | 2x-4+x=28 | | 24=-8u+5(u+6) | | 2x^2+2y^2-2xy-2x+4y+5=0 | | 3x^2+27x-6.5=0 | | 8(x-3)+9=5x+3(-4+x) | | 15-27=2(21) | | 5w=6w+7 | | .65x+18.50=.75x+18.50 | | 5s+8t=70 | | 6x^3-x^2-27x-20=0 | | (-81)/(+9)= | | n^2+3n-12-6=0 | | 2x^2-5x^2+5x-2=0 | | 0.01x+3.97=2.04x-2.12 | | -2x+4-2x=12 | | -2b+7=11 | | n^2+7n+15-5=0 | | (3u^2)-u-10=0 | | 200-25p=0 | | x(1.8+x)=.19 | | -5(x+1)+14=-3x+1 | | 3iz-z(1+i)-4i=0 | | 9x-16-3x=26 | | y^2-5y-x+9=0 | | t^2=5r | | 5x-2x+x= |